Nursing-Care Delivery: An Islamic Appraisal of the Attitudinal Dispositions of Contemporary Muslim Nurses in Nigeria - Muhammad, Abubakar Yalwa (KWASU Journal of Religious Studies, 2018)
Islam is regarded as not just a religion but a complete way of life. That is because it is a comprehensive religion, encompassing guidelines for conducting all human affairs, both religious and mundane. It is in this direction that Islam has a lot to offer to the Nursing Profession. This paper appraises the attitudinal dispositions of contemporary Muslim Nurses in Nigeria in the light of Islamic provisions. Both descriptive and analytical research methods were used in the study. Information about the activities and attitude of contemporary Muslim Nurses in Nigeria were collected through oral interviews and administration of questionnaires. The study reveals that while some Muslims in the Nursing profession apply their knowledge of Islam and are meticulous in the delivery of services to their patients, there are some others who do not reflect the teachings of Islam in the discharge of their essential duties; and as such put up negative attitude. The study therefore concluded and suggested that there is the need for Muslim nurses to see their calling as a humanitarian service; and also as an act of ʿIbādah, for which they will be rewarded appropriately in the hereafter.